2003
DOI: 10.4049/jimmunol.171.12.6442
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Complementation in Female (BXSB × NZW)F2 Mice

Abstract: F1 hybrids among New Zealand Black (NZB), New Zealand White (NZW), and BXSB lupus-prone strains develop accelerated autoimmunity in both sexes regardless of the specific combination. To identify BXSB susceptibility loci in the absence of the Y chromosome accelerator of autoimmunity (Yaa) and to study the genetics of this complementation, genome-wide quantitative trait locus (QTL) mapping was performed on female (BXSB × NZW)F2 mice. Six QTL were identified on chromosomes 1, 4, 5, 6, 7, and 17. Survival mapped t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…Previous linkage analyses using autoimmune (NZB, MRL and BXSB) and non-autoimmune strains (NZW, C57BL and B10) did not test the combination of OPN allotypes as in the present study (MRL vs. C3H) [2,3,5] except of a few studies [4,6,17]. In the study of BXSB Â B10 crosses [4,17], to detect the loci with additive mode of inheritance in disease susceptibility might be difficult since authors used BXSB Â (B10 Â BXSB)F 1 or B10 Â (BXSB Â B10)F1 backcrosses, not F 2 crosses.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…Previous linkage analyses using autoimmune (NZB, MRL and BXSB) and non-autoimmune strains (NZW, C57BL and B10) did not test the combination of OPN allotypes as in the present study (MRL vs. C3H) [2,3,5] except of a few studies [4,6,17]. In the study of BXSB Â B10 crosses [4,17], to detect the loci with additive mode of inheritance in disease susceptibility might be difficult since authors used BXSB Â (B10 Â BXSB)F 1 or B10 Â (BXSB Â B10)F1 backcrosses, not F 2 crosses.…”
Section: Discussionmentioning
confidence: 67%
“…In the initial step of this study, three loci were found to be associated significantly with GN, and one of them, Agnm3, turned out to be a novel locus that did not share a chromosomal region with any lupus susceptibility loci reported previously [2][3][4][5][6]8], although some phenotypic loci referring to immune traits were reported such as Lprm4 (lymphoproliferation modifier 4, 54 cM) that was designated by spleen weight in MCN 2 mice [12] and Tsz1 (Thymus size 1, 56 cM) that was designated by thymus size [13]. It should be noted that another study using progenies from B6/lpr and MRL/lpr mice did not show any linkage of GN to Agnm3, even though we employed the same conditions for mouse breeding and histopathologic GN grading as in this study (Zhang et al, manuscript in preparation).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A logarithm of odds (LOD) was calculated using the LRMapqtl program. Composite interval mapping was performed using model 6 of the ZMapqtl program with options set at 2-dM intervals and a 10-cM window size, considering background loci that include unlinked and linked loci-positioned forward parameters (17,18). The experiment-wise significance level for each index was determined by analyzing 10,000 randomshuffling permutations of the actual data, and the results of chromosomes with significant and suggestive linkages (␣ Ͻ 0.01 and ␣ Ͻ 0.05, respectively) (19) for either index are shown below.…”
Section: Methodsmentioning
confidence: 99%